Efficacy of preharvest salicylic acid treatment on postharvest quality enhancement of Marian plums (Bouea oppositifolia (Roxb.) Meisn.) - Supapvanich, S.; Da, L.; Phakawan, J.; Techavuthiporn, C. (My University, 2026)
Marian plum (Bouea oppositifolia (Roxb.) Meisn.) is a tropical fruit tree that holds significant commercial importance in Southeast Asia. Softening and disease incidence are the main problems limiting the postharvest quality of the fruits. The purpose of this study was to determine the efficacy of preharvest salicylic acid (SA) spray on fruit quality maintenance during storage at room temperature (25±1°C). The fruits were preharvest sprayed with SA at concentrations of 0 (water), 1, 2, and 3 mM prior to harvest for 3 days. The finding showed that 3 mM SA evidently delayed the progression of fruit coloration from the time of harvest to the end of storage (day 8) in comparison to the control treatment. During storage, disease incidence in the 3 mM SA-treated fruits was not found in comparison to other treatments. All SA treatments reduced the magnitude of the weight loss increase. The 3 mM SA treatment delayed fruit softening, lipid membrane degradation, and an increase in total soluble solids, while maintaining a high level of total acidity. In addition, the application of 3 mM SA significantly increased the ferric reducing antioxidant potential, and all SA treatments effectively maintained free radical scavenging activity compared to the control treatment. In conclusion, preharvest SA spray at 3 mM prior to harvest is an effective approach to maintaining the postharvest quality of marian plums during storage.
Keywords: antioxidants; Marian plum; postharvest quality; salicylic acid; softening